Predicted Chemical Speciation Distribution of Uranium and Other Elements in Leaching Solution From Specific Uranium Deposit by Using CHEMSPEC Software - Ya-wen CHEN; Wan-qiang ZHOU; Zheng-bang LIU; Ning GUO; Yu-qing NIU; Xiang-yun WANG; Hai-cheng WENG; Chun-li LIU (He huaxue yu fangshe huaxue)
During the in-situ leaching process of uranium, both the chemical composition of the leaching solution and the in-situ hydrogeochemical conditions can affect the chemical speciation of uranium. The chemical speciation of uranium significantly impacts its physicochemical behaviors during the in-situ leaching process. In this study, a speciation analysis software called CHEMSPEC, developed by Peking University, was used to calculate the speciation and speciation distribution of uranium and other specific elements in the leaching solution of a certain uranium mine. The effects of key factors was investigated such as pH and initial uranium concentration on uranium speciation and its distribution. The results show that the chemical speciation of uranium is greatly influenced by pH and initial uranium concentration. Uranium can precipitate as rutherfordine at acidic conditions(pH≈5.0), and the amount of precipitation increases with the increment of initial uranium concentration. The rutherfordine precipitation can dissolve when pH increases to 5.5. Calcium and magnesium exist in the form of free Ca2+ and Mg2+ under strong acidic conditions, and they can form dolomite and magnesite precipitates when pH＞6.6. The dominant speciation of bicarbonate salts exists as water-soluble CO2 under acidic conditions, and they transform into \begin{document}${CO}_3^{2-} $\end{document} under alkaline conditions. The carbonate species that participate in the precipitation of magnesite and dolomite under alkaline conditions constitute only about 5% of the total amount. Sulfur is in the form of free \begin{document}${SO}_4^{2-} $\end{document} in the in-situ leaching solution system under the studied pH conditions, and its speciation distribution is less relevant to pH. The speciation distribution of uranium and other characteristic elements in the in-situ leaching solution and the possible precipitates that may form are of great significance in improving the leaching efficiency of uranium.